2017
DOI: 10.32477/jkb.v23i2.209
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Motivasi Kerja Terhadap Kinerja Pegawai Kantor Sekretariat Daerah Kabupaten Gunungkidul

Abstract: This paper will discuss the effect of work motivation (incentives, motives and expectations) on the performance of the staff of the Regional Secretariat Gunungkidul. The purpose of this paper is: 1) Determine the effect of incentives on the performance of the staff of the Regional Secretariat Gunungkidul, 2) Determine the effect of motive on the performance of the staff of the Regional Secretariat Gunungkidul, 3) To know the effect of expectations on the performance of the staff of the Regional Secretariat Gun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 0 publications
0
4
0
10
Order By: Relevance
“…This type of research data consists of primary data and secondary data. According to Sutrischastini and Riyanto (2015) primary data is information obtained by reseaechers through direct investigation of the symptoms or from the source, while secondary data is from the source, while secondary data is information obtained by a researcher through other sources, both oral and written.…”
Section: Methodsmentioning
confidence: 99%
“…This type of research data consists of primary data and secondary data. According to Sutrischastini and Riyanto (2015) primary data is information obtained by reseaechers through direct investigation of the symptoms or from the source, while secondary data is from the source, while secondary data is information obtained by a researcher through other sources, both oral and written.…”
Section: Methodsmentioning
confidence: 99%
“…In accordance with the theory put forward by (Sutrischastini & Riyanto, 2015) argues that motivation is the provision of motive power that creates the excitement of one's work, so that they are willing to work together productively to achieve and realize the specified goals. 6) Based on the results of statistical calculations, it can be concluded that the construct of work discipline has a significant positive effect on the construct of employee performance directly.…”
Section: Resultsmentioning
confidence: 68%
“…A. P. Mangkunegara, 2016) Motive is an encouragement in employees that needs to be met so that employees can adjust to their environment, while motivation is a condition that moves employees to be able to achieve the goals of their motives. According to Hasibuan, quoted by (Sutrischastini & Riyanto, 2015) stated that motivation is the provision of movement that creates the excitement of one's work, so that they want to work together productively to achieve and realize the specified goals. Based on the theory above, it can be concluded that motivation is as a power resource that drives and controls human behavior.…”
Section: Motivation Theorymentioning
confidence: 99%
“…Salah satu faktor penting yang mendorong setiap orang dalam melakukan pekerjaan dengan penuh tanggung jawab adalah motivasi kerja (Andriani et al, 2018;Sutrischastini & Riyanto, 2015). Motivasi kerja seorang guru membawa guru menuju pencapaian tujuan pendidikan yang sehingga berdampak positif terhadap kinerja yang maksimal (Sudarjat et al, 2015).…”
Section: Pembahasanunclassified